Cordon Tolling in a City with Congested Bridges - Jan K. Brueckner (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper analyzes cordon tolling using a simple model where space is discrete rather than continuous, with commuting costs incurred only on two congested bridges. The first-best regime requires tolls on both bridges, whereas only the inner bridge is tolled under the cordon-toll regime. While less realistic than the continuous-space frameworks used in previous work, this simple setup allows the derivation of a number of analytical results, which were mostly unavailable to authors relying on more-complex models. The paper derives the rule for the optimal cordon toll, showing that it points to a toll level higher than first-best toll on the same bridge. In addition, the analysis shows that cordon tolling leads to a redistribution of population away from the zone immediately outside the cordon, with residents moving to the central zone or to the suburbs. The analysis also shows that the cordon toll raises more revenue than is necessary to pay for the bridge where it is levied, while also tending to increase the capacity of the untolled suburban bridge.
Keywords: R41; 330; toll; cordon; congestion